MiR-205-driven downregulation of cholesterol biosynthesis through SQLE-inhibition identifies therapeutic vulnerability in aggressive prostate cancer - Kalogirou, Charis Alexis Thomas; Linxweiler, J.; Schmucker, P.; Snæbjörnsson, Marteinn; Schmitz, W.; Wach, S.; Krebs, M.; Hartmann, E.; Puhr, M.; Müller, A.; Spahn, M.; Seitz, A. K.; et al. (Nature Communications, 2021)
Prostate cancer (PCa) shows strong dependence on the androgen receptor (AR) pathway. Here, we show that squalene epoxidase (SQLE), an enzyme of the cholesterol biosynthesis pathway, is overexpressed in advanced PCa and its expression correlates with poor survival. SQLE expression is controlled by micro-RNA 205 (miR-205), which is significantly downregulated in advanced PCa. Restoration of miR-205 expression or competitive inhibition of SQLE led to inhibition of de novo cholesterol biosynthesis. Furthermore, SQLE was essential for proliferation of AR-positive PCa cell lines, including abiraterone or enzalutamide resistant derivatives, and blocked transactivation of the AR pathway. Inhibition of SQLE with the FDA approved antifungal drug terbinafine also efficiently blocked orthotopic tumour growth in mice. Finally, terbinafine reduced levels of prostate specific antigen (PSA) in three out of four late-stage PCa patients. These results highlight SQLE as a therapeutic target for the treatment of advanced PCa.